2006
DOI: 10.1105/tpc.106.041798
|View full text |Cite
|
Sign up to set email alerts
|

AGL24,SHORT VEGETATIVE PHASE, andAPETALA1Redundantly ControlAGAMOUSduring Early Stages of Flower Development inArabidopsis

Abstract: Loss-of-function alleles of AGAMOUS-LIKE24 (AGL24) and SHORT VEGETATIVE PHASE (SVP) revealed that these two similar MADS box genes have opposite functions in controlling the floral transition in Arabidopsis thaliana, with AGL24 functioning as a promoter and SVP as a repressor. AGL24 promotes inflorescence identity, and its expression is downregulated by APETALA1 (AP1) and LEAFY to establish floral meristem identity. Here, we combine the two mutants to generate the agl24 svp double mutant. Analysis of flowering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
208
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 217 publications
(228 citation statements)
references
References 43 publications
15
208
1
4
Order By: Relevance
“…Indeed, recent studies have shown that most genes of this family are expressed in several plant tissues, organs, and developmental stages (Kofuji et al, 2003;Parenicová et al, 2003;Schmid et al, 2005). Other studies suggest that MADS-box functional specificity may depend on combinatorial protein-protein interactions (Egea-Cortines et al, 1999;Honma and Goto, 2001;de Folter et al, 2005;Kaufmann et al, 2005;Gregis et al, 2006;Sridhar et al, 2006), rather than on specific spatiotemporal expression patterns for each gene determined at the transcriptional level, as had been suggested before (Savidge et al, 1995;Alvarez-Buylla et al, 2000a).…”
Section: Discussionmentioning
confidence: 72%
“…Indeed, recent studies have shown that most genes of this family are expressed in several plant tissues, organs, and developmental stages (Kofuji et al, 2003;Parenicová et al, 2003;Schmid et al, 2005). Other studies suggest that MADS-box functional specificity may depend on combinatorial protein-protein interactions (Egea-Cortines et al, 1999;Honma and Goto, 2001;de Folter et al, 2005;Kaufmann et al, 2005;Gregis et al, 2006;Sridhar et al, 2006), rather than on specific spatiotemporal expression patterns for each gene determined at the transcriptional level, as had been suggested before (Savidge et al, 1995;Alvarez-Buylla et al, 2000a).…”
Section: Discussionmentioning
confidence: 72%
“…complex to repress AGAMOUS during floral development (Gregis et al, 2006). Similar interactions between SVP-like and AP1-like proteins may be important for floral development in cereals and other grasses.…”
Section: Discussionmentioning
confidence: 99%
“…This peculiar arrangement of BPC and MADS domain binding sites suggests that these factors might interact to facilitate binding to this promoter region. To investigate this further, we tested by yeast two-, three-, and four-hybrid experiments whether BPC proteins were able to interact with the AP1-SVP-SEU-LUG corepressor complex (Gregis et al, 2006). First, we tested by yeast two-hybrid assays the interactions between BPC1, BPC2, and BPC3, all cloned as BD fusions, with AP1, LUG, SEU, and SVP, all cloned as AD fusions.…”
Section: Bpc Factors Facilitate the Binding Of The Ap1-svp-seu-lug Rementioning
confidence: 99%
“…This complex is important to repress homeotic gene expression during the first stages of flower development to prevent precocious differentiation of the floral meristem into floral organs. For instance, it was shown that SVP and AP1 directly bind and repress MADS box floral organ identity genes, such as APE-TALA3 (AP3), PISTILLATA (PI), SEPALLATA3 (SEP3), and AG-AMOUS (AG) (Gregis et al, 2006;Gregis et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation